Life cycle assessment of animal-based foods and plant-based protein-rich alternatives: an environmental perspective - Detzel, A.; Kruger, M.; Busch, M.; Blanco Gutiérrez, I.; Varela Ortega, C.; Manners, Rhys; Bez, J.; Zannini, E. (Wiley, 2022)
BACKGROUND In the European Union proteins for food are largely animal based, consisting of meat and dairy products. Almost all soy but also a larger part of pulses and cereals consumed in the European Union are used for animal nutrition. While livestock is an important source of proteins, it also creates substantial environmental impacts. The food and feed system is closely linked to the planetary and health boundaries and a transformation to healthy diets will require substantial dietary shifts towards healthy foods, such as nuts, fruits, vegetables and legumes.